A comparison of blue and silver vertically-suspended environmental enrichment during Chinook Salmon and Rainbow trout rearing - Michael J Robidoux; Thomas Mauck; Nathan Huysman; Jill M Voorhees; Michael E Barnes (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2022)
This study evaluated the use of either blue or silver vertically-suspended environmental enrichment in two experiments, with one rearing Chinook salmon (Oncorhynchus tshawytscha) for 29 days and the other rearing rainbow trout (Oncorhynchus mykiss) for 98 days. In both experiments, there were no significant differences in total tank weight, gain, percent gain, feed conversion ratio, or percent mortality between tanks with either silver (unpainted aluminum) or blue vertically-suspended environmental enrichment. Individual fish total length, weight, specific growth rate, and condition factor were also not significantly different between the two colors for both fish species. These results indicate that either silver (unpainted aluminum) or blue vertically-suspended environmental enrichment can be used during the hatchery rearing of juvenile Chinook salmon or rainbow trout.